The location and elevation of Syowa Station, Antarctica - Katsutada Kaminuma (Antarctic Record, 1993)
Many reports concerning the locations and elevations of Syowa Station, Antarctica, have been published. Here previous data are noted for future reference. All data presented in this report were surveyed from the astronomical geodetic point which was established in 1957. The details are as follows : 1) The locations of meteorological and geomagnetic observations are used the location of the astrnomical geodetic point. 2) The locations of the pendulum gravity station and seismic vault were determined by surveying and leveling from the astronomical geodetic point. 3) The locations of the gravity point in the Earth Science Laboratory, the absolute gravity point and the tide gauge were determined from the geographical map of East Ongul Island (1 : 5000), Antarctica. Elevations of those points were determined by leveling from the tide gauge reference point.